Nicht ohne unsere Nachbarn ... Paradigmenwechsel in der europäischen Infrastrukturpolitik des Verkehrs? - Nowak, Herwig (Deutscher Verkehrs-Verl., 2006)
Vor wenigen Monaten hat die von der Europäischen Kommission eingesetzte High Level Group "Wider Europe for Transport" ihren Abschlussbericht vorgelegt. Mit ihm wird eine neue Kenngröße in die Europäische Infrastrukturpolitik eingeführt und zum Planungsmaßstab erhoben: die Nachbarschaftspolitik. difu

The transport-related infrastructure policies of the EU are being revised according to new criteria. Accordingly, to foster good neighbourly relations, the transport- related infrastructure policies of the EU are to be orientated towards those new neighbours, which share a border with the EU since its expansion on 1 May 2004, by giving due consideration to their transport requirements. No less than 27 states are involved, including Algeria, Armenia, Azerbijan, Belarus, Israel, Libya, Morocco, Palestine, Ukraine etc. Led by the former EU Transport Commissioner Loyola de Palacio, a top level group has given priority status to five major international transport routes linking the new neighbours with the EU while also providing access to the interior of the countries concerned. Certain sections of these traffic arteries have been selected for expansion and completion on a priority basis in line with their pre-determined roles. Some of these routes form part of major trans-European transport corridors, others function separately. In all, this reaches far beyond the transport functions taken into account in the case of the - rather distant - countries in question. As yet, there is no comprehensive plan for the financial back-up needed in support of infrastructure-related policies. difu
Keywords: Verkehr; Verkehrspolitik; Verkehrsinfrastruktur; Infrastrukturpolitik; Verkehrssystem; Verkehrsplanung; Straßenverkehr; Straßennetz; Fernverkehr; Europa; Grenzüberschreitender Verkehr